Peningkatan Hasil Belajar Melalui Model Pembelajaran Jigsaw - Koto, Erniwati (JURNAL GLOBAL EDUKASI, 2018)
Abstract: The subjects of this study were 30 students in grade 3 Semester II of Academic Year 2017/2018, consisting of 21 male students and 9 female students. The results of the learning evaluation from the pre cycle, cycle I and cycle II always increase and it can be seen from the percentage of students who complete in learning at the time of the pre cycle there is 30%, then the first cycle there is 60% and the second cycle there is 93.3%. From the results of the second cycle as a whole, it can be stated that classroom action research carried out in SD Negeri 074045 Saewe, Gunungsitoli South Gunungsitoli Subdistrict, academic year 2017/2018 has succeeded in achieving a predetermined success indicator of 85%. Keywords: Learning Outcomes, Jigsaw Learning Abstrak: Subyek penelitian ini adalah siswa kelas 3 Semester II Tahun Pelajaran 2017/2018 yang berjumlah sebanyak 30 anak, yang terdiri dari 21 siswa laki- laki dan 9 siswa perempuan. Hasil evaluasi pembelajaran dari pra siklus, siklus I dan siklus II selalu meningkat dan itu dapat dilihat dari prosentase siswa yang tuntas dalam mengikuti pembelajaran pada waktu pra siklus ada 30%, kemudian siklus I ada 60% dan siklus II ada 93,3%. Dari hasil pada siklus II secara keseluruhan maka dapat dinyatakan bahwa penelitian tindakan kelas yang dilaksanakan di SD Negeri 074045 Saewe Kecamatan Gunungsitoli Selatan Kota Gunungsitoli Tahun Pelajaran 2017/2018 telah berhasil mencapai indikator keberhasilan yang telah ditetapkan yaitu 85%. Kata kunci: Hasil Belajar, Jigsaw Learning